Aproximación a un modelo de aprovisionamiento de servicios convergentes (2014)
In the last thirty years telecom service provisioning has changed significantly. In the early years, there were static and rigid provisioning models and these were controlled by only one business actor. After that, a new flexible and dynamic provisioning models with a lot stakeholder in the value chain appeared in the telecom market. Approaches have proposed service provisioning models for telecom operator; however, it’s not clear what process have to carry out in each services lifecycle phase in order to integrate different service provisioning models in an efficient way. In this paper, we present an approach to initial model of convergent services provisioning emphasizing in those generic processes inside of design, deployment and operation service. Moreover, we built an automatic mechanism for initial deployment in a convergent environment based on the process defined in that service phase. Finally, we validate that automatic mechanism with a scalability test.